Microbial Lipid Production from Corn Stover by the Oleaginous Yeast Rhodosporidium toruloides Using the PreSSLP Process - Xiaozan Dai; Hongwei Shen; Qiang Li; Kamal Rasool; Qian Wang; Xue Yu; Lei Wang; Jie Bao; Dayu Yu; Zongbao K. Zhao (Energies, 2019)
Dry acid pretreatment and biodetoxification (DryPB) has been considered as an advanced technology to treat lignocellulosic materials for improved downstream bioconversion. In this study, the lipid production from DryPB corn stover was investigated by the oleaginous yeast Rhodosporidium toruloides using a new process designated prehydrolysis followed by simultaneous saccharification and lipid production (PreSSLP). The results found that prehydrolysis at 50 °C and then lipid production at 30 °C improved lipid yield by more than 17.0% compared with those without a prehydrolysis step. The highest lipid yield of 0.080 g/g DryPB corn stover was achieved at a solid loading of 12.5%. The fatty acid distribution of lipid products was similar to those of conventional vegetable oils that are used for biodiesel production. Our results suggested that the integration of DryPB process and PreSSLP process can be explored as an improved technology for microbial lipid production from lignocellulosic materials.